The role of source and site effects on structural failures due to Azores earthquakes. (October 2015) - Estêvão, João M.C.; Carvalho, Alexandra
Highlights: The 1980 Azores earthquake was simulated with four different source characteristics. Nonlinear soil amplification of nine stratigraphic soil profiles was evaluated. The vulnerability of one RC building and two masonry buildings was studied. Earthquake damage was assessed. Relations between damage level and source and site characteristics were obtained. Abstract: The existing building stock in Azores islands (Portugal) was severely damaged during 1980 and 1998 earthquakes. Structural failure was probably caused by a combination of factors that are not yet well understood. Earthquake source characteristics, site effects and structural vulnerability may be some of those factors. However, it is very difficult to assess the influence of each factor on structural failure, mainly because recorded accelerograms used in nonlinear structural analysis are influenced by both source characteristics and site conditions. The only way to overcome this problem is to control each factor individually which can be done by using simulated accelerograms. In our previous work, stochastic ground motion simulations results were compared with earthquake records. Results seem to indicate that simulated accelerograms can match recorded accelerograms if proper source characteristics and geological site conditions are selected. In this work, simulated accelerograms were used for seismic nonlinear structural analysis. Simulations were carried out considering several 1980 Azores earthquake possible sources and for different geological site conditions. Simulated accelerograms were then used to evaluate the structural nonlinear behaviour of a reinforced concrete structure and of two masonry structures. The results of this work highlight the importance of site conditions and earthquake source characteristics to the determination of the design seismic actions of Azores islands. This work was performed in the scope of "Strong ground motion for Azores – SiGMA" project, financed by the Portuguese Science and Technology Foundation (PTDC/CTE-GIX/121957/2010).